2000
DOI: 10.1016/s0735-1097(00)00643-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic characteristics of left atrial spontaneous echo contrast in sinus rhythm

Abstract: Spontaneous echo contrast in NSR occurs in patients with significantly dilated LA and depressed atrial function. Left atrial thrombus is noted in 13% of such patients despite NSR. Spontaneous echo contrast in NSR is associated with a higher prevalence of CVA. Further, SEC is found to be an independent and more powerful correlate of CVA than reduced LAAEV or atrial size. These data indicate that LASEC in NSR is a prothombotic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 26 publications
1
70
2
Order By: Relevance
“…21,[23][24][25] SEC was present in Ϸ45% of our patients with atrial fibrillation, which is slightly lower than described previously. 23,26 This can be explained by the inclusion of patients with intermittent atrial fibrillation in this subgroup.…”
Section: Clinical Implications Of Cardiac High-risk Sources In Teecontrasting
confidence: 61%
“…21,[23][24][25] SEC was present in Ϸ45% of our patients with atrial fibrillation, which is slightly lower than described previously. 23,26 This can be explained by the inclusion of patients with intermittent atrial fibrillation in this subgroup.…”
Section: Clinical Implications Of Cardiac High-risk Sources In Teecontrasting
confidence: 61%
“…Previous studies have identified spontaneous echocardiographic contrast as a marker of electromechanical atrial dysfunction and a risk factor for arrhythmia recurrence after DCCV. [9][10][11] We speculate that spontaneous echocardiographic contrast may identify patients with more advanced atrial dysfunction and hence a poor response to DCCV. Antiarrhythmic drug (AAD) therapy is an alternative or adjunct to DCCV for restoring sinus rhythm in patients with atrial arrhythmia.…”
Section: Discussionmentioning
confidence: 92%
“…In a review of 1288 TEE studies of patients in sinus rhythm (1), the incidence of spontaneous echo contrast was 21%; 13% of these patients had an associated left atrial thrombus. All patients had an enlarged left atrium and reduced peak LAA emptying velocity (1).…”
Section: Discussionmentioning
confidence: 99%